(untitled) (International journal of artificial intelligence, 2025)
This article explores the relevance of using medicinal plants in the treatment of upper respiratory tract diseases, emphasizing their place in both traditional and modern medicine. The pharmacological effects of the biologically active compounds in these plants, their therapeutic benefits, and precautions are thoroughly discussed. The article particularly analyzes several widely used medicinal plants in Uzbek folk medicine, presenting practical applications for respiratory health.